HUBUNGAN ANTARA PENGETAHUAN IBU TENTANG PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI DENGAN SIKAP IBU DALAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI DI WILAYAH KERJA PUSKESMAS BENDAN KOTA PEKALONGAN - Ta’adi, Ta’adi; Amirudin, Zaenal; Fitriyah, Nur (JURNAL LITBANG KOTA PEKALONGAN, 2016)
MATERNAL MORTALITY RATE (MMR) REFERS TO THE NUMBER OF MATERNAL DEATHS RELATED TO PREGNANCY, CHILDBIRTH, AND POSTPARTUM (PRASETYAWATI, 2012; P. 3). THE DIRECT CAUSES OF MATERNAL MORTALITY IS APPROXIMATELY 90% ARE CAUSED BY ABOUT CHILDBIRTH, AND THESE DEATHS OCCUR DUE TO COMPLICATIONS (PRASETYAWATI, 2012; P14). CAUSES OF MATERNAL MORTALITY ONE OF WHICH IS THE FACTOR OF DELAY, NAMELY THE DELAY IN THE DECISION TO SEEK HEALTH CARE, DELAY IN REACHING HEALTH CENTERS, AND DELAYS IN RECEIVING HEALTH CARE. ONE BREAKTHROUGH EFFORTS AND PROVEN TO IMPROVE THE INDICATORS OF DELIVERY BY HEALTH PERSONNEL IN A DECREASE IN MMR AND IMR IS P4K. BIRTH PLANS TO DO WHEN THE MOTHER, HUSBAND AND FAMILY HAVE KNOWLEDGE ABOUT DANGER SIGNS OF PREGNANCY, CHILDBIRTH AND POSTPARTUM. THE RESEARCH OBJECTIVE WAS TO DETERMINE THE RELATIONSHIP BETWEEN MATERNAL KNOWLEDGE ABOUT P4K WITH THE ATTITUDE OF THE MOTHER IN P4K IN PUSKESMAS BENDAN PEKALONGAN. THE STUDY WAS DESCRIPTIVE CORRELATIVE WITH CROSS SECTIONAL APPROACH. POPULATION OF 257 PREGNANT WOMEN WITH A SAMPLE OF 65 RESPONDENTS OBTAINED THROUGH A SIMPLE RANDOM SAMPLING TECHNIQUE. TEST ANALYSIS USED WERE UNIVARIATE AND BIVARIATE ANALYSIS USING SPEARMAN RANK. THE RESULT SHOWED THAT MOST RESPONDENTS HAVE GOOD KNOWLEDGE ABOUT P4K (70.8%), MORE THAN 50% OF RESPONDENTS HAVE A POSITIVE ATTITUDE IN P4K (58.5%), TEST RESULTS OBTAINED STATISTICALLY SIGNIFICANT VALUE OF 0.003 (LESS THAN Α = 0, 05) TO RS 0,361. THIS SHOWS THERE IS A SIGNIFICANT RELATIONSHIP WITH THE CLOSENESS OF THE RELATIONSHIP IS WEAK. SUGGESTIONS RESEARCH IS EXPECTED TO BE MORE MOTIVATED PREGNANT WOMAN LOOKING FOR INFORMATION ABOUT P4K THAT CAN BE OBTAINED FROM THE ELECTRONIC PRINT MEDIA, EDUCATION OF HEALTH PROFESSIONALS AS WELL AS MATERNAL AND CHILD HEALTH BOOK IN ORDER TO IMPROVE THE KNOWLEDGE OF THE MOTHER BECAME GOOD KNOWLEDGE AND A POSITIVE ATTITUDE SO THAT IT CAN EARLY IN THE BIRTH PLAN.